Roman Figural Bronzes from Religious Contexts in Northern Italy (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2016)
This paper takes into account, for the regions of northern Italy (Aemilia excluded), bronze and lead figural objects of small and medium size, found presumably in places of worship of Roman imperial period, and some stone votive inscriptions perhaps in connection with metal figurines, now lost. The aim is to outline the presence or absence of bronzes in shrines (and in some public but not religious buildings) and deduce possible indications. The investigation is therefore limited to one aspect of the ritual and can not lead by itself to the knowledge of religions arising from the integration of all sources; also the collected data are certainly incomplete, because of the vastness of the considered area and the dispersion of the bibliography. Some remarkable complex of bronzes with accurate catalogues are particularly rich in information.
Keywords: figural bronzes; places of worship; roman imperial period; northern Italy